2007
DOI: 10.1103/physrevlett.98.230503
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Multiqubit Entanglement via a Spin Bus

Abstract: We propose an experimentally feasible architecture with controllable long-range couplings built up from local exchange interactions. The scheme consists of a spin-bus, with strong, always-on interactions, coupled dynamically to external qubits of the Loss and DiVincenzo type. Long-range correlations are enabled by a spectral gap occurring in a finite-size chain. The bus can also form a hub for multiqubit entangling operations. We show how multiqubit gates may be used to efficiently generate W -states (an impor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
133
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 29 publications
1
133
0
Order By: Relevance
“…Scaling up the spin-qubit architecture invariably requires on-chip quantum information transfer, whether via moving the electrons themselves [9][10][11] or via a "spin bus". 12 However, electron motion could lead to reduced spin coherence, 13 while the spin bus requires strong exchange couplings within a spin chain. An enticing alternative to move spin information is to transfer it coherently to a photon, which is mobile and decoherence-resistant.…”
Section: Introductionmentioning
confidence: 99%
“…Scaling up the spin-qubit architecture invariably requires on-chip quantum information transfer, whether via moving the electrons themselves [9][10][11] or via a "spin bus". 12 However, electron motion could lead to reduced spin coherence, 13 while the spin bus requires strong exchange couplings within a spin chain. An enticing alternative to move spin information is to transfer it coherently to a photon, which is mobile and decoherence-resistant.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to implementing long-range interactions typically involve identifying a system that acts as a mediator of the interaction between the qubits, with proposed systems including optical cavities and microwave stripline resonators [21][22][23][24][25][26], floating metallic [27] and ferromagnetic [28] couplers, the collective modes of spin chains [29][30][31], superconducting systems [32,33], and multi-electron molecular cores [34]. Recently, long-range coupling of electrons located in the two outer quantum dots of a linear triple dot system has been demonstrated [35,36].…”
mentioning
confidence: 99%
“…Entanglement properties in two-dimensional AFM models have been studied [8] and it has been shown that multiqubit entanglement can be generated efficiently via a quantum data bus consisting of spin chains with strong static AFM couplings [9,10]. The effects of fluctuating exchange couplings and magnetic fields on the fidelity of data bus transfer have also been investigated [11].…”
Section: Introductionmentioning
confidence: 99%